2015
DOI: 10.1080/10426507.2014.947405
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Some Novel 1-(Substituted Phenyl)-2-(4-(Trimethylsilyl)-1H-1,2,3-Triazol-1-YL) Ketones

Abstract: R: substituted phenyl, R 1 : H, CH 3 . Abstract A facile and highly efficient method for the regioselective one-pot synthesis of a series of novel 1-(substituted phenyl)-2-(4-(trimethylsilyl)-1H-1,2,3-triazol-1-yl)ketones from 2-bromo-1-(substituted phenyl)ketones, sodium azide, and trimethylsilyl acetylene, through Cu (I) catalyzed 1,3-dipolar [3+2] cycloaddition reaction is reported. The reaction proceeds smoothly in 40% aqueous

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…[36][37][38] Similarly, organosilicon reagents have proven useful in various Cu-and Pd-catalysed C-X bond forming strategies, [39][40][41][42][43][44][45][46][47] including widespread use across several CuAAC methodologies. [48][49][50] Germanium-based functional groups have recently emerged as highly useful components for transition metal-catalysed crosscouplings. Schoenebeck and co-workers have shown that Gebased compounds are versatile reagents for chemoselective cross-coupling processes for the formation of a variety of C-C and C-X bonds.…”
mentioning
confidence: 99%
“…[36][37][38] Similarly, organosilicon reagents have proven useful in various Cu-and Pd-catalysed C-X bond forming strategies, [39][40][41][42][43][44][45][46][47] including widespread use across several CuAAC methodologies. [48][49][50] Germanium-based functional groups have recently emerged as highly useful components for transition metal-catalysed crosscouplings. Schoenebeck and co-workers have shown that Gebased compounds are versatile reagents for chemoselective cross-coupling processes for the formation of a variety of C-C and C-X bonds.…”
mentioning
confidence: 99%